Mode Division Multiplexing of LG and HG modes in Ro-FSO - Angela Amphawan; Sushank Chaudhary; Hafiza Samad; Jihadah Ahmad (IAES Indonesia Section, 2015)
Radio-over-free-space-optics (Ro-FSO) is a strongcontender for providing a ubiquitous platform for seamlessintegration of high capacity radio and optical networks withoutexpensive optical fiber cabling. This work presents mode divisionmultiplexing of LG and HG modes in a 40 GHz Ro-FSOtransmission system to realize 4 x 20Gbps over a free space opticallink under clear weather conditions. The signal-to-noise-ratio,received power and constellations will be analyzed.